Bagaimana Kepuasan kerja dipengaruhi oleh The Big Five Personality di Hotel Padma Semarang - Putri, Bunga Permata; Hadi, Syamsyul (ITB AAS Indonesia Surakarta, 2024)
Human resources are the most valuable and important assets owned by an organization/company. This research aims to reveal employee job satisfaction which is influenced by The Big Five Personalities. This research was conducted at the Padma Hotel using 106 respondents from 144 current employees. This research uses a quantitative approach, namely an associative approach, which focuses on analysis to determine the relationship between two or more variables, and aims to quantitatively estimate the magnitude of the influence of changes in one or more events. From the results of the data processing and analysis carried out several conclusions were obtained. namely the five dimensions of The Big Five Personality partially influence employee job satisfaction. Likewise, the results of simultaneous testing concluded that the five dimensions of The Big Five Personality simultaneously influence job satisfaction. Key Words : Job Satisfaction, The Big Five Personality